2020
DOI: 10.3390/jcm9061959
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Disease Progression in Early-Stage COVID-19 Patients in South Korea

Abstract: A rapid increase in the number of patients with coronavirus disease 19 (COVID-19) may overwhelm the available medical resources. We aimed to evaluate risk factors for disease severity in the early stages of COVID-19. The cohort comprised 293 patients with COVID-19 from 5 March 2020, to 18 March 2020. The Korea Centers for Disease Control and Prevention (KCDC) classification system was used to triage patients. The clinical course was summarized, including the impact of drugs (angiotensin II receptor blockers [A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 36 publications
2
33
0
Order By: Relevance
“…In line with our results, five observational studies reported no evidence of a harmful effect of NSAID use on COVID-19 severity among patients with COVID-19 33–36 but most were of much smaller sample size and not all were general population based, limiting generalisability. 34 A case–control study that investigated the association between renin–angiotensin–aldosterone system blockers and COVID-19 diagnosis found no association between NSAIDs and COVID-19 diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…In line with our results, five observational studies reported no evidence of a harmful effect of NSAID use on COVID-19 severity among patients with COVID-19 33–36 but most were of much smaller sample size and not all were general population based, limiting generalisability. 34 A case–control study that investigated the association between renin–angiotensin–aldosterone system blockers and COVID-19 diagnosis found no association between NSAIDs and COVID-19 diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…In line with our results, three observational studies reported no evidence of a harmful effect of NSAID use on COVID-19 severity among patients with COVID-19 3537 but they were of much smaller sample size and not all were general population based, limiting generalisability. 36 A population-based case-control study which investigated the association between renin-angiotensin-aldosterone system blockers and COVID-19 diagnosis found no association between NSAIDs and COVID-19 diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Severe disease. Ten studies reported severe disease as an outcome in COVID-19 patients (19,(54)(55)(56)(57)(58)(59)(60)(61)(62). The definition of severe disease, however, varied among studies.…”
Section: Resultsmentioning
confidence: 99%